Fiqih Perjudian: Analisis Terhadap Lotere dan Undian Dari Perspektif Syariah - Nurmaini, Nurmaini; Winario, Mohd (EL-EMIR Institute, 2024)
This research aims to analyze lotteries and sweepstakes from a sharia perspective. The main focus is to understand how Islamic law views this activity, examine the opinions of ulama, as well as evaluate the social and economic impact of lotteries and raffles in the context of Muslim society. The research method used is qualitative with a descriptive and comparative approach. A descriptive approach is used to provide a detailed description of the practice of lotteries and lotteries, while a comparative approach is used to compare the views of various schools of thought in Islam regarding lotteries and lotteries. Data was collected through literature studies from primary and secondary sources, such as fiqh books, interpretations of the Al-Quran, Hadith, and contemporary fatwas. The research results show that lotteries and raffles are categorized as a form of gambling (maysir) which is prohibited in Islam. This prohibition is based on sharia principles which prioritize benefit and avoid damage. The Koran and Hadith explicitly mention that gambling is an act of Satan that can cause hostility and hatred. The views of scholars such as Yusuf Al-Qaradawi, Wahbah Al-Zuhayli, and Sheikh Muhammad bin Salih Al-Utsaimin agree that lotteries are haram because they contain elements of speculation and uncertainty which are contrary to sharia. From a socioeconomic perspective, gambling brings more harm than good, including financial loss, family breakdown, and negative impacts on social well-being. Strict implementation of sharia law and education and public awareness efforts are essential to reduce the negative impacts of gambling.